A National Survey of Obstetric Early Warning Systems in the United Kingdom: 5 Years On. Issue 3 (September 2015) - Isaacs, R.A.; Wee, M.Y.; Bick, D.E.; Beake, S.; Sheppard, Z.A.; Thomas, S.; Hundley, V.; Smith, G.B.; van Teijlingen, E.; Thomas, P.W.
Abstract : ( Anaesthesia . 2014;69(7):687–692)